The Identification of New Histamine Derivatives in the Skin of Leptodactylus - Erspamer, V. (1964)
Extracts of the skin of some South American amphibians belonging to the genus Leptodactylus contain, in addition to 5-hydroxyindolealkylamines and hydroxyphenylalkylamines, remarkable amounts of imidazolealkylamines. The species most rich in these compounds are Leptodactylus pentadactylus labyrinthicus and Leptodactylus laticeps. The skin of the former species contains not only histamine, N'-methyl- histamine and N', N'-dimethylhistamine but also two imidazo-c-pyridine derivatives hitherto unknown in nature: spinaceamine and 6-methylspinaceamine. The new findings permit a notable enlargement of our knowledge in the field of biogenic imidazolealkylamines and illustrate new possible metabolic pathways for histamine.